PENGARUH MODEL GAME BASED LEARNING BERBANTU DIORAMA TERHADAP PEMAHAMAN KONSEP IPA SISWA KELAS IV SD - Susanti, Dita; Nurjamaludin, Muhammad; Nadiroti Muslihah, Neni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the effect of a Game-Based Learning model assisted by diorama media on fourth-grade students' understanding of science concepts at SDN 3 Leuwigoong. The participants were Class IV-A as the experimental group, which received Game-Based Learning assisted by diorama media, and Class IV-B as the control group, which received conventional instruction. Data were collected through science concept understanding test administered to both groups. The data were analyzed using an independent sample t-test at a significance level of 0.05 and an N-Gain test. The results showed a significance value of 0.022 <0.05, indicating a significant difference between the groups. The N-Gain analysis revealed an average improvement score of 0.653 in the experimental group and 0.503 in the control group. Therefore, the Game-Based Learning model assisted by diorama media was more effective in improving students" understanding of science concepts.